Determinação molecular da viabilidade do Mycobacterium leprae: uma comparação com outras abordagens metodológicas - Sartori, Beatriz Gomes Carreira [UNESP] (2015)
Access to information about the disease, its diagnosis and treatment with multidrug therapy (MDT) are constituted as key elements of the strategy for its control. Result of infection by Mycobacterium leprae (M. leprae), leprosy is a chronic disease that affects the skin and nerves and the impossibility of cultivating M. leprae in axenic culture medium, has hampered in vitro studies and the development of clinical trials show is complicated by the slow progression of the bacillus. Thus, a sensitive and specific method for detection of viable M. leprae add a fair criterion to the means already available, allowing diagnosis even in early stage disease. This study aimed at evaluating the bacterial viability by specific 16S rRNA detection for M. leprae with the normalization of the total quantities of mycobacteria from the quantification of total DNA of M. leprae. It was used as a standard inoculation into the footpads of mice (Shepard Technique). Patients were evaluated prior to treatment and relapses in patients suspected to treatment. The inoculation was highly positive in untreated patients compared to the relapse groups and end of treatment. The results suggest that there is a good correlation between the data obtained from inoculation and molecular assay, since it was also possible to detect levels of 16S rRNA and RLEP these samples. This methodology may in the future help monitor the effectiveness of treatment and the search for new possibilities for the study of host-parasite interaction